Protected at work but not at home: para-occupational ‘take-home’ herbicide residue exposure risks amongst forestry workers families in South Africa - Pududu, Bonolo (Department of Public Health and Family Medicine, 2019)
Para-occupational 'take-home’ exposure amongst worker’s families in Low-and middle-income countries (LMICs) is not well characterised. This is concerning as research shows the association between long-term low-dose herbicide exposure and the development of adverse health effects. This study explored 'take-home’ herbicide residue exposure risks amongst the families of Working for Water (WfW) forestry workers in the Western Cape, South Africa using aspects of the community-based participatory research (CBPR) approach photovoice. In addition, a documentary review of the existing WfW programme policies and regulations was undertaken to assess whether required practices supported or prevented the risk of 'taking-home’ herbicide residues. The results of the documentary review revealed that workplace policies and regulations did not address 'take-home’ exposure risks. Photovoice findings highlighted low compliance to safety practices (e.g., not adhering to PPE requirements) at worksites, and this was identified as the main risk factor for 'take-home’ exposure amongst worker’s families. It was noted that the transient nature of forestry work impacted on worker’s ability to carry out hygiene practices as decontamination facilities were not available at worksites for worker’s to use before going home. As a result, all workers took their personal protective equipment (PPE) home. Worker’s after work behaviours (e.g., wearing PPE inside the home) and home hygiene practices (e.g., laundering PPE separately from household laundry) varied. That is, some worker’s carried out protective practices whilst others did not. This was largely attributed to the workplace policies and regulations which did not cover 'take-home’ exposure risks as informed by the national legislation which has not established standards and regulations related to 'take-home’ exposure risks. Evidence from this study demonstrated the existence of workers’ 'taking-home’ herbicide residue and exposing their families to potential health risks from low-dose exposures.